Portrait of Rabbi Judah Wechsler of Mt. Zion Temple (Jewish Historical Society of the Upper Midwest, 4330 S. Cedar Lake Road, Minneapolis, MN 55416. http://www.jhsum.org/asp_pages/index.asp, 1870)
ac7230b51f91d4e1e65dcfa2c1413a5c
Rabbi Wechsler (pronounced Wexler) lead the congregation's sponsoring a Jewish farming settlement in the Dakota Territories. The settlement attempted to help Russian Jewish immigrants find livelihoods working the land in the American West. Though the farm colony ultimately failed, he was considered an innovator and modernizer. Late in his career, after leaving Minnesota, he worked to improve educational opportunities in Mississippi for blacks. He served at tm Zion from 1878-1886.
United States
Minnesota
Ramsey
St. Paul
Mode of access: Internet.
Keywords: Portraits; Rabbis; Mt. Zion Congregation; Religion